Long-term Results of Troublesome CWD Cavity Reconstruction by Mastoid and Epitympanic Bony Obliteration (CWR-BOT) in Adults. Issue 6 (July 2016) - Vercruysse, Jean-Philippe; van Dinther, Joost J. S.; De Foer, Bert; Casselman, Jan; Somers, Thomas; Zarowski, Andrzej; Cremers, Cor C.; Offeciers, Erwin
Abstract : Objective: To present the long-term surgical outcome of the bony mastoid and epitympanic obliteration technique with canal wall reconstruction (CWR-BOT) in adults with an unstable cavity after previous canal wall-down surgery for extensive cholesteatoma. Study Design: Retrospective study. Interventions: Therapeutic. Setting: Tertiary referral center. Patients: Fifty consecutive adult patients undergoing a CWR-BOT between 1998 and 2009. Main Outcome Measure(s): (A) Recurrence and residual rates of cholesteatoma, (B) postoperative hygienic status of the ear, including postoperative aspect of the tympanic membrane and external ear canal integrity (EAC), (C) functional outcome, and (D) long-term safety issues. Results: (A) The percentage of ears remaining safe without recurrent or residual disease after CWR-BOT was 96% after a mean follow-up time of 101.8 months. Recurrent cholesteatoma occurred in 2% (n = 1) and a residual cholesteatoma was detected in 2% (n = 1) of the patients. (B) A safe dry, and trouble-free graft and selfcleaning EAC was achieved in 94%. (C) The postoperative hearing results showed a gain of 1.7 dB on pure-tone average air-conduction. (D) Nonecho planar diffusion-weighted imaging (non-EP DW magnetic resonance imaging) documented the residual (n = 1) and recurrent cholesteatoma (n = 1). The 1- and 5-year imaging follow-up revealed no other recurrent or residual disease. Conclusion: The CWR-BOT is a safe and very effective option for treatment of problematic unstable canal wall-down mastoid cavities, resulting in dry trouble-free ears.